Evaluation of sexual function in females with exstrophy-epispadias-complex: A survey of the multicenter German CURE-Net. Issue 2 (April 2017) - Ebert, Anne-Karoline; Lange, Theresa; Reutter, Heiko; Jenetzky, Ekkehart; Stein, Raimund; Boemers, Thomas M.; Hirsch, Karin; Rösch, Wolfgang H.; Zwink, Nadine
Summary: Objective: Standardized knowledge about genital function in adult female individuals with exstrophy-epispadias complex (EEC) is scarce. The aim of this study was to investigate sexual function using the standardized Female Sexual Function Index (FSFI), and to assess the influence of bladder and vaginal reconstruction and the presence of incontinence on FSFI results. Method: Sixty-one females (aged ≥18 years) recruited by the German multicenter network for congenital uro-rectal malformations (CURE-Net) were asked to complete the FSFI and a self-designed semi-structured questionnaire assessing comprehensive medical data, gynecological, and psychosocial items. Twenty-one eligible females (34%) returned both questionnaires (mean ± standard deviation [SD] age of 26 ± 5.1 years). Results: In 43% of participants, a staged or single-staged approach had been used for reconstruction, and these had their bladder in use. A primary or secondary urinary diversion (UD) after cystectomy had been performed in 38% of participants. Of the participants, 57% lived in a committed partnership, and 62% had sexual intercourse on a regular basis, with a further 19% experiencing pain or discomfort thereby. Introitus plasty was done in 43%. Mean total FSFI for all participants was 21.3 (SD 1.9). Most domain scores of patients after introitus plasty were similar compared with those without an operative vaginal approach, except for satisfaction ( p  = 0.057) and pain ( p  = 0.024). Comparing incontinent with continent patients, significant differences were found for desire (mean 4.6 vs. 3.5, p  = 0.021), lubrication (mean 3.1 vs. 4.2, p  = 0.049), and satisfaction (mean 1.6 vs. 3.6, p  = 0.0065). In contrast pain was not significant between groups. Conclusions: Sexual activity rate in the present study was similar to that reported in the literature (81% vs. 89%), whereas dyspareunia rate was lower in our cohort (19% vs. 24%). The risk for sexual dysfunction seems to be lower in patients reconstructed with primary or secondary UD than patients with bladder in use. It is surprising that lubrification was better after UD than after bladder neck surgery. Incontinence and in some parts the history of an introitus plasty may play an additional role in development of sexual dysfunction in EEC. Although most of the female EEC patients lived in a committed partnership and had sexual intercourse, total FSFI values <26.55 clearly indicate a risk of sexual dysfunction. Although continence itself played a major role, females reconstructed with UD seem to have better sexual function. Further evaluation of sexual outcome and improvement of care for these patients is mandatory.